Analytics, Data Science, and Artificial Intelligence : Systems for Decision Support - Sharda, Ramesh, author 452453; Delen, Dursun, author 391433; Turban, Efraim, author 241637; Pearson Education Limited (Online service) 647098 (Harlow : Pearson Education, Limited, 2020)
This title is a Pearson Global Edition. The Editorial team at Pearson has worked closely with educators around the world to include content which is especially relevant to students outside the United States. For courses in decision support systems, computerized decision-making tools, and management support systems.Market-leading guide to modern analytics, for better business decisionsAnalytics, Data Science, & Artificial Intelligence: Systems for Decision Supportis the most comprehensive introduction to technologies collectively calledanalytics(orbusiness analytics) and the fundamental methods, techniques, and software used to design and develop these systems. Students gain inspiration from examples of organizations that have employed analytics to make decisions, while leveraging the resources of a companion website. With six new chapters, the11th editionmarks a major reorganization reflecting a new focus -- analytics and its enabling technologies, including AI, machine-learning, robotics, chatbots, and IoT.Give students anytime, anywhere access with Pearson eTextPearson eTextis a simple-to-use, mobile-optimized, personalized reading experience available within MyLab. It lets students highlight, take notes, and review key vocabulary all in one place - even when offline. Pearson eText can also be adopted on its own as the main course material.Learn moreabout Pearson eText orcontact your Pearson repfor purchase options.